Perceived benefits and barriers of using online journal systems - Mwantimwa, Kelefa; Wema, Evans F (University of Dar es Salaam Library Journal, 2022)
This study has established the perceived benefits and barriers of using online journal systems (OJS). A descriptive research design alongside a quantitative approach was used to establish perceived benefits and barriers of using online journal systems among University of Dar es Salaam faculty members. In the study data were gathered through survey questionnaires. The data were then organized and summarized through descriptive statistics in form of frequencies and percentages. The study reveals that a significant number of faculty members infrequently use the systems in their scholarly communication. Along this, the study reveals various benefits of using OJS as perceived by faculty members. The study also reveals diverse perceived barriers that undermine effective use of the systems. These include low internet bandwidth and technical difficulties. The study recommends that the UDSM has to take deliberate measures to enhance internet services through increasing bandwidth, alongside increasing training on the use of online journal systems.